The impact of preoperative sarcopenia on postoperative complications following esophagectomy for esophageal neoplasia: a systematic review and meta-analysis. Issue 7 (20th March 2020) - Papaconstantinou, Dimitrios; Vretakakou, Konstantina; Paspala, Anna; Misiakos, Evangelos P; Charalampopoulos, Anestis; Nastos, Constantinos; Patapis, Paul; Pikoulis, Emmanouil
Summary: Esophageal cancer is characterized by profound changes in body composition due to dysphagia and generalized cachexia. Sarcopenia or muscle wasting is a component of cachexia associated with poor postoperative performance status. The skeletal muscle index (SMI) calculated by computed tomography scans at the level of the third lumbar vertebra is an easily quantifiable and reproducible measure of sarcopenia. The aim of this meta-analysis is to investigate the impact of preoperative sarcopenia (low SMI) on postoperative complications after esophagectomy for neoplastic lesions. In this context, a comprehensive literature search was undertaken to identify studies reporting short-term postoperative outcomes in relation to their preoperative SMI values. Cumulative risk ratios (RR) and risk differences (RD) and their respective 95% confidence intervals (CIs) were calculated using a random-effect model. A total of 11 studies incorporating 1, 979 total patients (964 patients with sarcopeniaversus 1, 015 without sarcopenia) were included in the final analysis. The results demonstrated a significant increase in overall morbidity (RR 1.16, 95% CI 1.01–1.33), respiratory complications (RR 1.64, 95% CI 1.21–2.22) and anastomotic leaks (RR 1.39, 95% CI 1.10–1.76) in patients with sarcopenia. No statistically significant difference was noted in overall mortality (RD 0, 95% CI −0.02–0.02) or Clavien–Dindo grade III or greater complications (RR 1.17, 95% CI 0.96–1.42). The above results demonstrate the validity of the SMI as a predictive factor for post-esophagectomy complications. Although the risk associated with sarcopenia is not prohibitive for surgery, patients with low SMI require closer vigilance during their postoperative course due to the increased propensity for respiratory and anastomotic complications.